REFLECTIONS ON CASH FLOW IN THE EVALUATION OF PROJECTS - Andía V., Walter (2003)
The present articles seeks to provide and set some guidelines for a suitable use of the tools used in Projects Evaluation, especially with regard to Cash Flow.